OPTIMIZATION OF ATHLETES’ MENTAL SELF-REGULATION UNDER CONDITIONS OF SPORTS RESTRICTIONS DURING THE COVID-19 PANDEMIC - Lovyagina, A.E.; Syrykh, I.K.; Tiunova, O.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and test a mental self-regulation optimization program for athletes under conditions of restrictions due to the COVID-19 pandemic. Methods and structure of the study. Participants were athletes (men and women) engaged in different sports. The questionnaire "Difficulties of self-regulation in conditions of self-isolation" and the questionnaire of self-government by Y. Kul and A. Furman were used in the study. A program of mental self-regulation for athletes being involved in training and competition activities has been developed based on the psychodiagnostic data analysis. The experimental group of athletes included the program in their preparation, control group trained in the usual mode. A comparative analysis of mental self-regulation among control and experimental groups was conducted. Results and conclusions. The effectiveness of athletes’ mental self-regulation in COVID-19 pandemic conditions depends on the level of formation of planning, self-motivation and volitional regulation. Classes on the program significantly increased the effectiveness of athletes’ mental self-regulation. The classes were aimed at improving goal setting, self-motivation of doing sports and persistence in difficult situations during training and competition activities.